Advancing the implementation of artificial intelligence in regulatory frameworks for chemical safety assessment by defining robust readiness criteria - de Paula Souza, Joyce; Blum, Jonathan; Maran, Uko; Sild, Sulev; Dawson, Louis; Čavoški, Aleksandra; Holden, Laura; Lee, Robert; Karnel, Veronika; Meusburger, Lukas; Fraize-Frontier, Sandrine; Walsh, Alexander; et al. (Frontiers in Artificial Intelligence, 2026)
The integration of artificial intelligence (AI) into chemical risk assessment (CRA) is emerging as a powerful approach to enhance the interpretation of complex toxicological data and accelerate safety evaluations. However, the regulatory uptake of AI remains limited due to concerns about transparency, explainability, and trustworthiness. The European Partnership for the Assessment of Risks from Chemicals (PARC) project ReadyAI was established to address these challenges by developing a readiness scoring system to evaluate the maturity and regulatory applicability of AI-based models in CRA. The project unites a multidisciplinary consortium of academic, regulatory, and legal experts to define transparent and reproducible criteria encompassing data curation, model development, validation, explainability, and uncertainty quantification. Current efforts focus on identifying key priorities, including harmonized terminology, rigorous data quality standards, case studies, and targeted training of regulatory scientists. ReadyAI aims to deliver a practical, evidence-based scoring system that enables regulators to assess whether AI tools are sufficiently reliable for decision-making and guides developers toward compliance with regulatory expectations. By bridging the gap between AI innovation and regulatory applicability, ReadyAI contributes to the responsible integration of AI into chemical safety assessment frameworks, ultimately supporting human and environmental health protection.